The Canadian urban housebuilding industry: Firm size structure and production methods in Ontario, 1945--2000 - Buzzelli, Michael D. (My University, 2001)
The North American housebuilding industry is central to the production of urban space and the provision of housing. Yet surprisingly, housebuilding has received little scholarly attention in the housing, urban studies and industrial organisation literatures. Most of the major studies of the industry appeared in the early postwar years. These early studies interpreted the industry in terms of the preferred model of industrial organisation at the time, a model based on Fordist economies of scale, vertical integration and a highly segmented division of labour. Housebuilding's many small firms, labour intensive methods and subcontracting seemed underdeveloped, even backward, to observers. However, recent industrial restructuring has called into question the superiority of Fordist methods and permits a reinterpretation of housebuilding. This thesis provides such a reinterpretation based on a review of the organisation of housebuilding in North America since WWII and a case study of the industry in Ontario and its major urban region, Toronto. The case studies of Ontario and Toronto are based on quantitative and qualitative data sources and are combined with published and unpublished sources on housebuilding throughout North America since WWII. The principal sources used in this study are Canadian industry trade journals, a census of builders in the Province of Ontario from 1978 through 1998 provided by the Ontario New Home Warranty Program, and corporate interviews with a selection of builders in the Toronto region. As in North America since WWII, the case studies of Ontario and Toronto show that housebuilding remains a deconcentrated industry of small and transient firms. Entrepreneurs face few barriers to entry primarily because they can rely on a decentralised social system of production subcontracting. This permits a constant stream of new firms but also supplies many of the eventual exits as well. As such, housebuilding remains persistently deconcentrated while its firms experience constant turnover. On these grounds, criticisms of housebuilding by early observers are well-founded. Firm transience in an industry which supplies the most important commodity to the majority of North Americans continues to be a serious problem. However, interpretations of the small building company and its production methods as backwards were misplaced. Observers failed to appreciate the importance of the conditions of production and the market for new houses. The need to move production from site to site, to accommodate varied housing styles, weather, climate and market cyclicality all have consistently made production subcontracting an attractive method of operation. Indeed, many of the long-criticised features of housebuilding have come to be debated, and endorsed, in the literature on industrial restructuring in recent decades. For these reasons, housebuilding cannot be interpreted as backwards. This study joins a growing body of literature which argues against the notion of an optimal end state to industrial development. Industrial organisation may vary through time and across space. In remaining persistently deconcentrated by many small firms using extensive subcontracting methods, housebuilders merely represent efficient responses to the product and market conditions they face.
Keywords: Geography; Geology; Geography